Cancer Publications in One Year (2022): A Cross-Sectional Study - Fenk Mariwan Mohemed; Binaiy Nasih Fatih; Abdullah Abdulrahman Qadir; Shalaw H. Abdalla; Zana H. Mahmood (Barw Medical Journal, 2023)
AbstractIntroductionCancer is the uncontrollable and abnormal division of cells in a specific part of the body, which can spread to adjacent areas. The number of scientific publications on cancer has increased significantly over the past few decades. The objective of the current study is to evaluate scientific publications on cancer in 2022.MethodsA cross-sectional study was conducted on published papers on cancer in 2022. The data were collected online from the Google Scholar search engine and recorded in Microsoft Excel 2010. The extracted data were calculated and thoroughly re-evaluated, and they were presented as frequencies and percentages.ResultsA total of 167,129 medical studies on cancer in various body organs were collected for the study, with 37,500 studies specifically focused on breast cancer. This represented the highest number of studies in 2022, while only 4 articles were specific to glottis cancer, marking the lowest number in that year.ConclusionThe existence of a gap between the incidence rate of each cancer type and scientific literature may lead to a defect in our understanding of the nature of the diseases.